2013
DOI: 10.1504/ijss.2013.058227
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of impacts of employee engagement on continuance and normative commitment

Abstract: A positive relationship between employee engagement and affective commitment is already documented in the literature. However, we do not adequately know how engagement is associated with continuance and normative commitment. Using survey methodology we find that while engagement has a non-significant positive association with continuance commitment; it has a positive association with normative commitment. No negative association was found between engagement and continuance commitment. These results advance pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
10
0
3
Order By: Relevance
“…Nahrgang, Morgeson and Hofmann (2011) explain further by stating that employee engagement involves the level of commitment and involvement of employees towards an organisation and its values. In the same vein, Ortiz et al (2013) define employee engagement as a psychological state where employees feel they do have a vested interest in the organisation's success and perform to high standards that exceed the stated job requirements. Another definition by AbuKhalifeh and Som (2013) describes employee engagement as comprising positive attitude, passion and commitment to the organisation, its values and willingness to help other colleagues.…”
Section: Concept Of Employee Engagementmentioning
confidence: 99%
“…Nahrgang, Morgeson and Hofmann (2011) explain further by stating that employee engagement involves the level of commitment and involvement of employees towards an organisation and its values. In the same vein, Ortiz et al (2013) define employee engagement as a psychological state where employees feel they do have a vested interest in the organisation's success and perform to high standards that exceed the stated job requirements. Another definition by AbuKhalifeh and Som (2013) describes employee engagement as comprising positive attitude, passion and commitment to the organisation, its values and willingness to help other colleagues.…”
Section: Concept Of Employee Engagementmentioning
confidence: 99%
“…Temuan ini mengindikasikan bahwa pekerja di bidang pengembangan teknologi informasi bekerja berdasarkan lingkungan kerja dan gaji yang mendukung. Hasil ini didukung dari hasil penelitian bahwa organizational commitment memiliki pengaruh negatif terhadap work engagement (Ortiz, et al, 2013). Berdasarkan hal tersebut mengindikasikan bahwa pengaruh organisasi tidak memberikan efek positif bagi beberapa individu, dapat dijelaskan bahwa masing-masing individu lebih memilih untuk mengembangkan diri menjadi pekerja lepas (freelancer) tanpa terikat oleh organisasi.…”
Section: Hasil Dan Pembahasanunclassified
“…It is because engaged employees help organizations serve customers better in terms of satisfaction, loyalty, productivity, and profit [180]. Moreover, they tend to be more satisfied with their jobs, committed, and loyal to their organizations [181] because they believe that they constitute a part of the organization [182]. Siddhanta & Roy [183] found that engagement makes employees more motivated and committed; thus, it positively affects organizational performance [182,[184][185][186][187][188][189][190][191][192][193].…”
Section: Engagementmentioning
confidence: 99%